THE RELATIONSHIP BETWEEN WORKLOAD AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE AT PT. ALLIANZ LIFE INSURANCE INDONESIA CRM DIVISION IN THE PANDEMIC PERIOD OF COVID-19 - Elizabet, Brigitta; Anggrain, Nenny (Universitas Kristen Indonesia, 2021)
The COVID-19 pandemic has an impact ranging from financial and non-financial impacts on companies. The success of a company in the COVID-19 pandemic condition is very dependent on the Human Resources in the company regardless of how much money the company gets. The research was conducted with the aim of finding out how the workload and work environment relate to the performance of the CRM division employees during the COVID-19 pandemic. The research was conducted at the PT. Allianz Life Insurance Indonesia, Jakarta. This research is descriptive quantitative by as many as 35 employees of the CRM division. This test uses statistical techniques of Sperman Rank Correlation and Multiple Correlation Pearson Moment. The results of this study show a significant positive result between workload and performance tcount (3.368)> ttable (2.034) with a Spearman Rank correlation value of 0.506 which means it is quite strong and positive. obtained positive significant results between the work environment and employee performance, the value of tcount (2.729)> ttable (2.034) and the Spearman Rank correlation value of 0.429 which means that it is quite strong and positive. It was found that the results of the calculation of workload variables and work environment have a strong significant relationship with employee performance, the tcount value of Fcount (5,654)> Ftable (2,036) and the results of the Pearson Product Moment multiple correlation test of (0.511) which have a strong value. Keyword: workload, work environment, employee performance.